Estimation of cancer risks during mammography procedure in Saudi Arabia - Sulieman, A. (Saudi J Biol Sci, 2019)
The aims of the present work were to quantify radiation doses arises from patients' exposure in mammographic X-ray imaging procedures and to estimate the radiation induced cancer risk. Sixty patients were evaluated using a calibrated digital mammography unit at King Khaled Hospital and Prince Sultan Center, Alkharj, Saudi Arabia. The average patient age (years) was 44.4 ± 10 (26–69). The average and range of exposure parameters were 29.1 ± 1.9 (24.0–33.0) and 78.4 ± 17.5 (28.0–173.0) for X-ray tube potential (kVp) and current multiplied by the exposure time (s) (mAs), respectively. The MGD (mGy) per single projection for craniocaudal (CC), Medio lateral oblique (MLO) and lateromedial (LM) was 1.02 ± 0.2 (0.4–1.8), 1.1 ± 0.3 (0.5–1.8), 1.1 ± 0.3 (0.5–1.9) per procedure, in that order. The average cancer risk per projection is 177 per million procedures. The cancer risk is significant during multiple image acquisition. The study revealed that 80% of the procedures with normal findings. However, precise justification is required especially for young patients.